Internships & intentions: A grounded theory study of a South African government graduate internship programme - Hendricks, Sumaya (University of the Witwatersrand, Johannesburg, 2024)
The researcher used a grounded theory approach to understand the factors which affected intern learning on a graduate internship programme run by the South African government, with a focus on one national government department. In particular, the focus was on understanding how factors worked to create a disjuncture between the intended and experienced curriculum. To conduct this research, interviews were conducted with interns who completed their internship in the 2018-2021 period; HR officials; and mentors – all of whom were based in the department of focus. This was complemented with document analysis and intern demographic data. While the interest in this subject matter was from a learning perspective, this programme is also a labour market intervention to help alter the bias towards these young, black and unemployed graduates who are the target audience of this programme. In this study, the central phenomenon that emerged is that of Curricular fission which is a metaphor to describe a situation in which various factors worked to create a rupture between what interns were intended to learn compared to what they actually learned. In short, the metaphorical large atom which caused the fission were institutional, individual and task related factors with these factors preventing interns from moving from legitimate peripheral participants to full participants. Institutional factors operated at the level of the department, individual factors concerned the individual - whether that be the intern themselves; the government officials that interns reported to; or other people interns interacted with - while task related factors were related to the tasks allocated to interns, which had a direct bearing on intern learning. While the interns had control over some of the factors, many were ‘beyond’ their control which reinforces the view of learning as being shaped, hindered or aided by factors beyond the learners themselves. With a situation of curricular fission characterising the overall intern learning experience, the programme could be considered a form of ‘warehousing’ which in a South African context carries a transformation component arising from the ‘special’ burden that workplaces have in addressing the bias towards black graduates.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Workplace curriculum; Workplace learning; Graduate internship; Government internship programme; Intern learning; Intended curriculum; Grounded theory; SDG-4: Quality education